POTENSI OBYEK WISATA DAN KETERPADUANNYA DALAM PENGEMBANGAN KAWASAN AGROPOLITAN PAYANGAN, KABUPATEN GIANYAR, PROVINSI BALI - I Kadek Pasek Rudita; Santun RP Sitorus; Setia hadi (http://arl.faperta.ipb.ac.id/, 2012)
Payangan Agropolitan is an area of agricultural development that has tourism potential. Along with development of the agricultural sector, the tourism sector also developed. However, recently trends that agriculture sector got tressured by the development of other sectors; one of them was the tourism sector. Thus, further developments need to be done in an integrated manner. Objectives of this research were: (1) to find out the potential of tourist attractions to be developed in the region of Payangan Agropolitan; (2) to find out the tourist's perception on the factors that effects tourist visitation to the Area of Payangan Agropolitan;(3)to formulate plans and strategies of integrated tourism development of Payangan Agropolitan in the framework of area development. Analysis on the tourism potential showed that the most preferred was nature-related tourism. From analysis of the factors of tourist visitation, there were five dominant influential factors, i.e: services, tourism and attraction types, the available facilities, transportation facilities, and promotion. Furthermore, on the subsequent analysis it was obtained three main strategies to integrate tourism with areadevelopment of Payangan Agropolitan, consisted of: improving the sectoral linkage by integrating of inter-existing sectors was developing science and technology; introducing and offering the existing tourism potential by developing tourism packages through a partnership of government, private and public; and strengthening the tourism by establishing partnerships and networks.